(untitled) (Quinto Sol, 2025)
This article studies the uses of the recent past in Entre Ríos’ political debate in the 1860s, analyzing the province’s federalist press. This period was marked by the hegemony of the Liberal Party led by Bartolomé Mitre, the decline of federalism as a political force and identity, and the erosion of Justo José de Urquiza’s leadership as the Federal Party’s supreme figure. In this context, the federalist press of Entre Ríos maintained a discourse of opposition to Mitre’s government and of defense of federalism, of the people of Entre Ríos, and of Urquiza. The arguments deployed in the newspaper articles appealed to events and figures from the past as a tool to understand the present and legitimize political positions. These heterogeneous and contradictory discourses sought to vindicate Entre Ríos’ role in the process of independence from Spain, in the opposition to the government of Juan Manuel de Rosas, and in the resistance to the interests of the city of Buenos Aires. These narratives differed from the interpretations of the past created in Buenos Aires, but they had several similarities in the interpretative cores and the figures evoked.